2018
DOI: 10.1111/jir.12542
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of burnout among professionals working with people with intellectual and developmental disabilities

Abstract: Most of these predictors are organisational measures. These findings demonstrate that organisational variables are more significantly associated with burnout of staff working with people with IDD than the socio-demographic factors or professional characteristics. Identifying and better understanding the specific factors associated with burnout among professionals working with IDD could facilitate unique intervention programs to reduce burnout levels in staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
(148 reference statements)
3
11
0
1
Order By: Relevance
“…These factors may contribute to coping with challenges in long‐term care. Our study and previous ones indicated that long‐term care relationships are important for understanding the behaviour of clients, but can also cause blind spots and impede a critical look at one's own professional behaviour (Bekkema, de Veer, Hertogh, & Francke, 2015; Donaldson & Grant‐Vallone, 2002; Finkelstein, Bachner, Greenberger, Brooks, & Tenenbaum, 2018; Iacono et al., 2014; Janssen & Van der Vegt, 2011; Murray, 2005). Previous research showed that strong bonds with clients and high engagement with work may lead to ID‐care staff taking on overly demanding responsibilities and refusing to admit mistakes in daily work (Donaldson & Grant‐Vallone, 2002; Janssen & Van der Vegt, 2011; Murray, 2005).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These factors may contribute to coping with challenges in long‐term care. Our study and previous ones indicated that long‐term care relationships are important for understanding the behaviour of clients, but can also cause blind spots and impede a critical look at one's own professional behaviour (Bekkema, de Veer, Hertogh, & Francke, 2015; Donaldson & Grant‐Vallone, 2002; Finkelstein, Bachner, Greenberger, Brooks, & Tenenbaum, 2018; Iacono et al., 2014; Janssen & Van der Vegt, 2011; Murray, 2005). Previous research showed that strong bonds with clients and high engagement with work may lead to ID‐care staff taking on overly demanding responsibilities and refusing to admit mistakes in daily work (Donaldson & Grant‐Vallone, 2002; Janssen & Van der Vegt, 2011; Murray, 2005).…”
Section: Discussionsupporting
confidence: 56%
“…These factors may contribute to coping with challenges in long-term care. Our study and previous ones indicated that long-term care relationships are important for understanding the behaviour of clients, but can also cause blind spots and impede a critical look at one's own professional behaviour (Bekkema, de Veer, Hertogh, & Francke, 2015;Donaldson & Grant-Vallone, 2002;Finkelstein, Bachner, Greenberger, Brooks, & Tenenbaum, 2018;Iacono et al, 2014;Janssen & Van der Vegt, 2011;Murray, 2005).…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, our finding of high engagement, involvement and dedication on the part of ID-care staff aligns with findings of previous studies among care professionals who have built longterm caring relationships with their clients. This largely differs from many other (dementia) care settings (Bekkema, de Veer, Hertogh, & Francke, 2015;Finkelstein, Bachner, Greenberger, Brooks, & Tenenbaum, 2018;Iacono et al, 2014;Wagemans, 2013). Such high self-esteem, and commitment to work may cause overestimation of their performance possibilities, reflected in taking on overly demanding responsibilities and refusing to admit mistakes in their jobs (Baumeister, Heatherton, & Tice, 1993;Donaldson & Grant-Vallone, 2002;Holtz & Gnambs, 2017;Janssen & Van der Vegt, 2011;Murray, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, if total referral rates continue to increase it will be imperative for services to allocate the appropriate resources to facilitate the adjustment in working intensity for staff members. A focus on workplace well-being should be taken as perceptions of unsurmountable increases in workload can lead to staff member burnout (Finkelstein et al, 2018). Moreover, as referral rates recover it is likely that waiting times will be maintained or lengthened.…”
Section: Referral Ratesmentioning
confidence: 99%